2020
DOI: 10.1101/2020.05.07.082313
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transcriptional comparison of Testicular Adrenal Rest Tumors with fetal and adult tissues

Abstract: Testicular Adrenal Rest Tumors (TART) are a common complication of unknown origin in patients with Congenital Adrenal Hyperplasia. These benign tumors may derive from cells of adrenal origin or from pluripotent progenitor cells from the fetal adrenogonadal primordium. By comparing the transcriptome of TART with fetal-and adulttestis and adrenal tissues, this study aims to unravel the origin of TART. Targeted transcriptome sequencing was followed by unsupervised clustering-, differential expression-, functional… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…Indeed, we showed undetectable, or very low (11OHA4), levels of CYP11B1-catalyzed steroids in adrenalectomized individuals, underscoring the dominance of adrenal (or adrenal-like) tissue in the production of 11oxC19 steroids. Although CYP11B1 has also been reported to be expressed in rat Leydig cells ( 21 ) or human testicular tissue ( 22 ), the expression levels are negligible compared to adrenal or TART tissue ( 23 , 24 ), which are in line with our transcriptome dataset including human testis, adrenal, and TART tissues ( 25 ).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Indeed, we showed undetectable, or very low (11OHA4), levels of CYP11B1-catalyzed steroids in adrenalectomized individuals, underscoring the dominance of adrenal (or adrenal-like) tissue in the production of 11oxC19 steroids. Although CYP11B1 has also been reported to be expressed in rat Leydig cells ( 21 ) or human testicular tissue ( 22 ), the expression levels are negligible compared to adrenal or TART tissue ( 23 , 24 ), which are in line with our transcriptome dataset including human testis, adrenal, and TART tissues ( 25 ).…”
Section: Discussionsupporting
confidence: 87%
“…To study the production of T by TART exclusively, we have also quantified T production by in vitro cultured TART cells and found that in vitro cultured TART cells produce greater amounts of T than cultured adrenal cells after ACTH stimulation, yet lower amounts of A4 and 11OHA4. The expression of the ACTH receptor MC2R and the Leydig cell enzyme HSD17B3 in TART cells ( 25 ) explains the ACTH-induced T production in TART, and the time course of T generation at 24 hours but 11OHT following at 48 hours is consistent with the pathway A4 to T to 11OHT. Thus, the relatively high elevation of 11OHT in the spermatic vein of patients with 21OHD and TART presumably indicates higher production and 11-oxygenation of T by TART.…”
Section: Discussionmentioning
confidence: 75%
“…Although the in utero environment might influence TART development, TART also rarely occurs with chronic ACTH elevation associated with acquired conditions (25,29,57) supporting the theory that TART originates from totipotent embryonic cells which grow when exposed to increased ACTH in utero (58) and early in life. However, TARTs from CAH patients and from patients with Cushing's disease were recently shown to have similar characteristics despite the different timing of excessive ACTH exposure (59). Using transcriptional analysis, Schröder et al showed higher transcriptional similarities of TART with adult adrenal tissues compared to fetal tissues suggesting that TART originates from a more distinct cell type rather than from a totipotent embryonic cell type (59).…”
Section: Discussionmentioning
confidence: 99%
“…However, TARTs from CAH patients and from patients with Cushing's disease were recently shown to have similar characteristics despite the different timing of excessive ACTH exposure (59). Using transcriptional analysis, Schröder et al showed higher transcriptional similarities of TART with adult adrenal tissues compared to fetal tissues suggesting that TART originates from a more distinct cell type rather than from a totipotent embryonic cell type (59). Our data from both IHC and transcriptomal profiling indicate that ART has both adrenal and gonadal-specific characteristics, supporting the theory that TART may originate from a totipotent cell with multi-differentiation ability.…”
Section: Discussionmentioning
confidence: 99%
“…In a new study published in this journal, Mariska Schröder and colleagues have helped further define the phenotype of TARTs and intriguingly shed some light on the possible cell of origin in these tumours (6). By performing double immunofluorescence in TART cells, the authors found that a proportion of TART cells co-expressed both 11- hydroxylase (adrenal specific and encoded by the CYP11B1 gene) and 17 -Hydroxysteroid dehydrogenase 3 (Leydig cell-specific, encoded by the HSD17B3 gene) indeed indicating the presence of "hybrid" cells with an adreno-testicular phenotype, rather than a heterogeneous population of separate adrenal-like and testicular-like cells within the tumour parenchyma.…”
mentioning
confidence: 99%